The Effect Of Tourism Attraction On Visitors Satisfaction In Tongke-Tongke Mangrove Forest Tourism Objects In Sinjai District - Nurhidayah, Nurhidayah; Niswaty, Risma; Kasmita, Maya (Jurnal Administrasi Bisnis, 2025)
This study aims to determine how the effect of tourist attraction on visitor satisfaction at the tongke-tonke mangrove forest tourist attraction, Sinjai district. To achieve these goals, researchers use indicators to measure these variables. On the tourist attraction variable with indicators of attraction (attractions), accessibility (accessibility), amenity (facilities), ancilliary (additional services). As for the visitor satisfaction variable with indicators of conformity to expectations, interest in visiting again, willingness to recommend. In this study, the research method used is quantitative method, with data collection techniques through observation, questionnaires, and documentation. The sample used was 100 respondents, resulting from the lemeshow formula. Data obtained from the research results and processed using data analysis and the help of the SPSS version 25 program which consists of validity and reliability tests, simple regression analysis and the coefficient of determination. The results showed that the indicators used in each variable, namely tourist attraction (X) and visitor satisfaction (Y) were in the good category. This shows that the tourist attraction variable has a positive and significant influence on visitor satisfaction at the tongke mnagrove forest tourist attraction, Sinjai district. This is evidenced based on the simple regression test and the coefficient of determination on the data obtained.